Using systems approaches to address challenges for clinical implementation of pharmacogenomics. (6th December 2013) - Karnes, Jason H.; Van Driest, Sara; Bowton, Erica A.; Weeke, Peter E.; Mosley, Jonathan D.; Peterson, Josh F.; Denny, Joshua C.; Roden, Dan M.
Abstract : Many genetic variants have been shown to affect drug response through changes in drug efficacy and likelihood of adverse effects. Much of pharmacogenomic science has focused on discovering and clinically implementing single gene variants with large effect sizes. Given the increasing complexities of drug responses and their variability, a systems approach may be enabling for discovery of new biology in this area. Further, systems approaches may be useful in addressing challenges in moving these data to clinical implementation, including creation of predictive models of drug response phenotypes, improved clinical decision‐making through complex biological models, improving strategies for integrating genomics into clinical practice, and evaluating the impact of implementation programs on public health. WIREs Syst Biol Med 2014, 6:125–135. doi: 10.1002/wsbm.1255 This article is categorized under: Translational, Genomic, and Systems Medicine > Translational Medicine